Pengaruh Pelatihan Canva terhadap Kreativitas Guru: Systematic Literature Review - azizi, bahrul; Muhid, Abdul (DIDAKTIKA : Jurnal Pemikiran Pendidikan, 2025)
This study aims to review the influence of Canva training on teacher creativity through a Systematic Literature Review (SLR) approach on 20 relevant articles. The analysis results show that Canva training significantly contributes to improving teachers' creativity, both in terms of technical skills and psychological aspects. Technically, Canva helps teachers design more innovative, interactive digital teaching materials that meet the demands of 21st-century learning. Teachers became more skilled in using Canva features to create teaching materials such as posters, videos, presentations, and student worksheets (LKPD). From a psychological perspective, Canva training has been proven to increase teachers' motivation, self-confidence, and readiness to innovate in learning. Additionally, the increase in teacher creativity through Canva directly impacts student engagement and learning outcomes. Some quantitative studies even show very significant contributions; for example, Canva training has an 88.1% effect on teacher creativity in elementary schools. However, the implementation of training still faces obstacles, such as limited devices, internet access, and differences in digital literacy among teachers. This evidence confirms the need for a systematic, continuous, and accompanied training strategy. Thus, Canva training can be considered an important instrument in the professional development of teachers, which not only enhances individual teacher creativity but also strengthens the quality of learning in the digital age and aligns with the Merdeka Curriculum.